2009
DOI: 10.1073/pnas.0903066106
|View full text |Cite|
|
Sign up to set email alerts
|

Site-specific regulation of cell cycle and DNA repair in post-mitotic GABA cells in schizophrenic versus bipolars

Abstract: GABA cell dysfunction in both schizophrenia (SZ) and bipolar disorder (BD) involves decreased GAD 67 expression, although this change involves fundamentally different networks of genes in the 2 disorders. One gene that is common to these 2 networks is cyclin D2, a key component of cell cycle regulation that shows increased expression in SZ, but decreased expression in BD. Because of the importance of cell cycle regulation in maintaining functional differentiation and DNA repair, the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 45 publications
4
39
0
1
Order By: Relevance
“…The DNA damage response in post-mitotic neurons includes cell-cycle arrest coupled with DNA repair, apoptosis, senescence and differentiation (Benes et al, 2009, Nguyen et al, 2002). However, the cell-cycle machinery, in general, and cell-cycle proteins active at the G1/S checkpoint may also contribute to terminal post-mitotic differentiation of neurons, early neuronal development, epigenetic regulation, signaling (ie., Wnt/β-catenin) and neuronal polarization (Lim and Kaldis, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA damage response in post-mitotic neurons includes cell-cycle arrest coupled with DNA repair, apoptosis, senescence and differentiation (Benes et al, 2009, Nguyen et al, 2002). However, the cell-cycle machinery, in general, and cell-cycle proteins active at the G1/S checkpoint may also contribute to terminal post-mitotic differentiation of neurons, early neuronal development, epigenetic regulation, signaling (ie., Wnt/β-catenin) and neuronal polarization (Lim and Kaldis, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This inf luence may extend beyond cortical development. These genes continue to be expressed in adult forebrain neurons and precursors (11), and may be part of larger cell-cycle regulatory networks that are differentially disrupted in schizophrenic and bipolar patients (46). Last, altered cell-cycle control in cortical precursors due to diminished 22q11 gene dosage may also contribute to increased tumorigenesis in 22q11 patients (47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that a network of 28 genes is associated with the regulation of glutamic acid decarboxylase 67 (GAD67) in the hippocampus and that this network interacts with other gene networks in maintaining genome integrity in specific neurons (Benes et al, 2009). GAD67, a marker for GABAergic neurons, is downregulated in the cortex and hippocampus of SZ and BP+ patients (Akbarian and Huang, 2006;Volk et al, 2000;Guidotti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…GAD67, a marker for GABAergic neurons, is downregulated in the cortex and hippocampus of SZ and BP+ patients (Akbarian and Huang, 2006;Volk et al, 2000;Guidotti et al, 2000). This gene cluster was uncovered during a network association analysis of cDNAs exhibiting compromised expression in CA3/2 hippocampal GABAergic neurons in SZ and BP disorder patients (Benes et al, 2009). The more recent study (Sheng et al, 2012) shows that there are highly significant changes in the magnitude and direction of individual gene copy number intensities in this GAD67 regulatory network.…”
Section: Introductionmentioning
confidence: 99%